Expanding the life-cycle model: Precautionary saving and public policy - Skinner, Jonathan; Hubbard, R. Glenn (American Economic Review, 1994)
One of the key puzzles in understanding behavior is not so much why people save-the title of this session-but why people don't save. According to the familiar life-cycle model, households should accumulate wealth to provide for their retirement consumption. The surprising result from the data is the sizable fraction of the population who have accumulated so little, even among those nearing retirement. Given that earnings will almost surely decline when households retire, such behavior can imply poor living standards for the elderly. Some might interpret the low wealth accumulation as being evidence of myopia, irrationality, or a failure of households to enforce mental accounting (Richard Thaler, 1994), while others might view the low level of wealth accumulation as evidence of high individual rates of time preference. Determining the underlying causes of low wealth is crucial for public policies that seek to alleviate low aggregate rates in the United States, as well as policies that seek to buttress the adequacy of financial resources for the elderly. In this paper, we outline what we believe to be the causes of why many people do not save. We conclude by speculating about government policies that may be most effective at encouraging saving. Much of the research examining levels of consumption, saving, and wealth, as well as their responsiveness to policy, has been done using a life-cycle model with the simplifying assumption of perfect certainty. Alan Auerbach and Laurence Kotlikoff (1987), for example, developed a model with 55 overlapping generations of individual lifecycle households, each with empirically plausible age-earnings profiles and utility parameters, and used the model to address tax policy and demographic issues in a regime in which all households are identical within a generation, and all generations know future earnings and interest rates. More recently, a line of inquiry has examined the effects of uncertainty on saving, generally in the context of highly stylized models. This research has shown that, in these models, uninsured earnings uncertainty can alter optimal behavior in a variety of important ways. (For a partial review of this precautionary saving literature, see Hubbard et al. [1994].) In two recent papers (Hubbard et al., 1993, 1994), we have combined these two strands of the literature by examining the implications of a life-cycle model of consumption, saving, and wealth accumulation subject to what we think are the three most important sources of uninsured idiosyncratic risk facing households: uncertainty about earnings, medical expenses, and length of life. Our intent has been to create a realistic model in which families live for many periods, working for part of their lives and retiring later in life. To parameterize the uncertainty facing families, we estimate tDiscussants: Christopher Carroll, Federal Reserve Board; John B. Shoven, Stanford University; Laurence Kotlikoff, Boston University.